2018
DOI: 10.1002/ecm.1311
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of avian pox and interaction with avian malaria in Hawaiian forest birds

Abstract: Despite the purported role of avian pox (Avipoxvirus spp.) in the decline of endemic Hawaiian birds, few studies have been conducted on the dynamics of this disease, its impact on free‐living avian populations, or its interactions with avian malaria (Plasmodium relictum). We conducted four longitudinal studies of 3–7 yr in length and used generalized linear models to evaluate cross‐sectional prevalence of active pox infection and individuals with healed deformities that had recovered from pox. Our goal was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
(277 reference statements)
1
16
0
Order By: Relevance
“…; Samuel et al. ; Ben‐Shachar and Koelle ). We included them in the Supporting Information (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…; Samuel et al. ; Ben‐Shachar and Koelle ). We included them in the Supporting Information (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly reported that poxvirus infection prevalence in wild birds increases after vector population peaks [34][35][36]. Poxvirus infection prevalence is lower at high altitudes, where vectors are less abundant [30,37,38].…”
Section: Epidemiologymentioning
confidence: 99%
“…Climatic changes observed in recent years induced increasing circulation of hematophagous arthropods, including mosquitos, in several geographic areas. Some authors observed that APV infection prevalence in wild birds increased after vector population peaks [32][33][34], and it was also lower at high altitudes, where arthropods were less abundant [35,36].…”
Section: Discussionmentioning
confidence: 99%